Kompleksitas Transfer Atlet Ilegal: Tantangan terhadap Integritas Penyelenggaraan Kejuaraan Daerah–Nasional dan Implementasi UU Nomor 11 Tahun 2022 - Ratu, Kornelis (SIGn Jurnal Hukum, 2025)
The practice of illegal athlete transfers is a latent problem that fundamentally threatens the integrity of competition and the sports development system in Indonesia. Despite the enactment of Law Number 11 of 2022, this practice persists due to the complexity of the issue, which has not been fully unraveled. This study aims to deconstruct the systemic pathology of illegal athlete transfers by analyzing the interconnection of the juridical, institutional, and socio-political factors that perpetuate it. Employing a socio-legal research method with a qualitative approach, this study examines statutory regulations, academic literature, and relevant case studies to investigate the topic. The findings indicate that the practice of illegal transfers is a symptom of three main pillars of weakness. First, regulatory fragmentation results from the conflict between national law and lex sportiva. Second, the dysfunction of oversight institutions and the absence of a centralized data infrastructure. Third, the functional paralysis of Law Number 11 of 2022 is due to the absence of specific and comprehensive implementing regulations governing inter-regional athlete transfer mechanisms. These weaknesses are actively exploited by a culture of politicization and patronage entrenched in sports governance. It is concluded that piecemeal reforms will not be effective. A comprehensive reform roadmap is required, encompassing regulatory harmonization, institutional strengthening, depoliticization, and the enhancement of legal literacy to build a sports ecosystem founded on integrity and accountability.